Crystal structure of {(S)-1-phenyl-N,N-bis[(pyridin-2-yl)methyl]ethanamine-κ3N,N′,N′′}bis(thiocyanato-κN)zinc from synchrotron data - Dong Won Lee (Acta Crystallographica Section E: Crystallographic Communications, 2017)
The title ZnII complex, [Zn(NCS)2(C20H21N3)], has been characterized by synchrotron single-crystal diffraction and FT–IR spectroscopy. The central ZnII ion has a distorted square-pyramidal coordination geometry, with three N atoms of the chiral (S) 1-phenyl-N,N-bis[(pyridin-2-yl)methyl]ethanamine (S-ppme) ligand and one N atom of a thiocyanate anion in the equatorial plane, and one N atom of another thiocyanate anion at the apical position. The average Zn—NS-ppme and Zn—NNCS bond lengths are 2.183 (2) and 1.986 (2) Å, respectively. In the crystal, intermolecular C—H...S hydrogen bonds and a face-to-face π–π interaction [centroid–centroid distance = 3.482 (1) Å] link the molecules and give rise to a supramolecular sheet structure parallel to the ac plane.